Bangkok, Creole City: War Slaves, Refugees, and the Transformation of Culture in Urban Southeast Asia. Issue 5 (May 2016) - Beemer, Bryce
Abstract: Slave‐gathering warfare was an endemic feature of Southeast Asian statecraft in the pre‐colonial era. In this lightly populated region, capturing people was more important than seizing new lands. Armies laid siege to rival urban centers and carried thousands of people into captivity, among them artisans, performers, and musicians. This is a well‐understood feature of Southeast Asian statecraft, but the histories of captive people have gone largely unstudied. My project is to examine slave‐gathering warfare as a vector for cultural exchange. The forced relocation of skilled people laid the groundwork for processes of transculturation and cultural reinvention, but the evidence of these exchanges lays mostly outside the archive in the artistic, musical, and theatrical practices of the captive communities themselves. In this article, I examine a cluster of neighborhoods in Thonburi, one of the oldest areas in metropolitan Bangkok. Descendants of non‐Thai war captives and refugees populate this area, most brought to Bangkok in the late‐18th and 19th centuries from Laos, coastal Burma, and the Malay border region. I examine the cultural practices that originated in these communities through the lens of creolization theory, which allows us to better examine and comprehend the cultural contribution of foreign captives to Bangkok's urban culture.